Genetic characterization of acute myeloid leukemia patients with mutations in IDH1/2 genes. (February 2021) - Acha, Pamela; Hoyos, Montserrat; Pratcorona, Marta; Fuster-Tormo, Francisco; Palomo, Laura; Ortega, Esther; Zamora, Lurdes; Vives, Susana; Granada, Isabel; Montoro, Julia; Garcia, Antoni; Arnan, Montserrat; et al.
Highlights: IDH1/2 cases account for 23% of the studied cohort. Mutual exclusivity was confirmed for IDH1 and IDH2 mutations. IDH1 (86%) and IDH2 (89%) mutations frequently constitute an ancestral event.